INCORPORATING GOOD LAND GOVERNANCE IN THE DISASTER REGION OF YOGYAKARTA - Sunarno, Sunarno (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2015)
Land is one of the most major capitals in our life. Without it, sustainability of human existence is very impossible. Unfortunately, land problems in Indonesia have unique challenges compared to other countries. Many of kinds of challenges are in the form of the natural disasters. This paper is going to measure how well the principles of good governance has been incorporated in the Yogyakarta Special Region Land administration System generally by studying on the Merapi Disaster Mitigation, particularly in how land planning for the Merapi Disaster’s victims is performed. The research methodology employs a combined research method, it means that fundamental principles in process and its output of both the doctrinal and non doctrinal approaches is synergized to based on the research’s activity unites. Configuration of the land administration systems in achieving people prosperity has been affected by evolution of political, cultural, and legal awareness of local communities and central government policy. To conclude, incorporating a disaster response based land policy principles requires an integrated law and policy making system among parties through the implementation of good governance principle in the record of public participation voices and sustainable development interests. Notable reports illustrate that the good land governance incorporation encouraged and inspired land planning system to be more efficient and effective. Particularly in the natural disaster mitigation and reconstruction, incorporating good land governance principles furthermore encourages land policy makers to achieve the responsive land management in line with social demands and sustainable development programs.